2020
DOI: 10.7759/cureus.9016
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Serum N-Terminal Pro-Brain Natriuretic Peptide and Endogenous Hydrogen Sulfide for Predicting Coronary Artery Lesions in Pediatric Kawasaki Disease Patients: Findings From a Tertiary Care Hospital in Karachi, Pakistan

Abstract: Introduction Kawasaki disease (KD) is an idiopathic, acute systemic vasculitis typically affecting medium-sized blood vessels with an inclination towards the coronary arteries. There is no specific diagnostic test established for it yet. Hence, our study aims to evaluate serum N-terminal pro-brain natriuretic peptide (NT-proBNP), hydrogen sulfide (H 2 S), and interleukin-6 (IL-6) levels as potential diagnostic tools in children with KD and determine its relationship with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…The report has showed that increased BNP predicts the risk of CAL in KD [9,10]. In our study, we found the level of BNP was signi cantly increased in CAL group of IVIG + IVMP group.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The report has showed that increased BNP predicts the risk of CAL in KD [9,10]. In our study, we found the level of BNP was signi cantly increased in CAL group of IVIG + IVMP group.…”
Section: Discussionsupporting
confidence: 60%
“…Studys have showed that brain natriuretic peptide (BNP) play a signi cant role in the pathogenesis of KD [8], and predicts the risk of CAL in Kawasaki disease [9,10]. In this study, we detected the level of BNP in IVIG + IVMP group with CAL and without CAL.…”
Section: Introductionmentioning
confidence: 67%